MODEL PENGEMBANGAN DESTINASI WISATA NIRWANA GARDEN BALI DI KABUPATEN JEMBRANA BERBASIS GREEN TOURISM DALAM MEWUJUDKAN PARIWISATA BERKELANJUTAN - Arya Wahyu Widiantara, I Putu; Budiarsa, Made; Darsana, I Made (Berajah Journal, 2025)
The decline in tourist visits and environmental management challenges at Nirwana Garden Bali highlight the need for a more sustainable development strategy. This study aims to analyze tourism development, identify the implementation of Green Tourism, and design a sustainable destination development model to enhance competitiveness and local community involvement. A qualitative approach was used to analyze the green tourism-based development model at Nirwana Garden Bali. The research was conducted in Jembrana Regency, Bali, with primary data collected through in-depth interviews, FGDs, observations, and open-ended questionnaires with managers, tourists, and local communities, while secondary data was obtained from official documents and scientific literature. The research instruments included interviews to explore management strategies, FGDs to assess social, economic, and environmental impacts, as well as observations and documentation analysis related to regulations. The findings indicate that Nirwana Garden Bali has the potential to become a sustainable tourism destination through the development of eco-friendly infrastructure and partnerships with local communities. The implementation of green tourism principles, such as energy efficiency, water management, and other environmentally friendly practices, supports sustainability. This development model adopts the Green Tourism Marketing (GTM) and Penthahelix concepts, which promote collaboration among various stakeholders to enhance destination competitiveness while preserving the natural and cultural heritage of Bali.